2018
DOI: 10.21708/avb.2018.12.1.7231
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vaquejada exercise on the physiological and biochemical profiles of sporadic competitors and atletic horses

Abstract: The aim of this study was to analyze the effect of a cycle of three races as a part of the vaquejada test, on the serum biochemistry of horses that compete sporadically and athletic horses. Fourteen Quarter Horses was evaluated: group 1 (G1), with seven horses from the region that competed sporadically and group 2 (G2), with seven horses that competed regulary and were transported for >200 km. The physiological and serum biochemistry parameters were evaluated before exercise (M0) and after a cycle of three rac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
1
3
0
3
Order By: Relevance
“…The results vary in the literature due to the differences for type, intensity and duration of the exercise carried out and physical conditioning of the animals and the different modalities (SOUZA et al, 2016). For example, similar results to the present study for CK and AST were observed by SOUSA et al (2018) in horses during vaquejada competition, both in a group of horses that competed sporadically and in a group of horses that did vaquejada regularly. The authors reported that in both groups there was a discrete non-significant raise for these enzymes immediately after sprinting, with later decrease of their concentration at 30 and 120 min., and at no time were there concentrations above normal limits.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…The results vary in the literature due to the differences for type, intensity and duration of the exercise carried out and physical conditioning of the animals and the different modalities (SOUZA et al, 2016). For example, similar results to the present study for CK and AST were observed by SOUSA et al (2018) in horses during vaquejada competition, both in a group of horses that competed sporadically and in a group of horses that did vaquejada regularly. The authors reported that in both groups there was a discrete non-significant raise for these enzymes immediately after sprinting, with later decrease of their concentration at 30 and 120 min., and at no time were there concentrations above normal limits.…”
Section: Resultssupporting
confidence: 66%
“…Opposite results were obtained to Lopes et al (2009) who did not find an significant increase in hematocrit of the horses after vaquejada. However, this increase has been described in some studies on horses after vaquejada exercise (BINDA et al 2016, SOUSA et al 2018, HUNKA et al 2018, and may be justified by the fact that the horses have a good reserve of erythrocytes in the spleen (6 to 12 liters), and this, responding to the stimuli that alter the sympathetic activity and release of catecholamines under the influence of the exercise, releases the erythrocytes to the blood, transporting oxygen in the erythrocytic hemoglobin to the tissues. This is reflected in the total red cell count, hematocrit, and hemoglobin concentration (WICKLER e ANDERSON, 2000).…”
Section: Resultsmentioning
confidence: 98%
“…The authors attribute the result to the good physical fitness of the animals (Santos et al 2015). Study with quarter horses during vaquejada exercise also did not find AST alteration (Sousa et al 2018).…”
Section: Discussionmentioning
confidence: 91%
“…Assessments of iron concentration were done in two groups of pull vaquejada horses, one that regularly performed with professional cowboys and in another group with amateur cowboys, and no variations in iron concentration were observed in each group or between groups after a vaquejada simulation test with three races [46]. On the other hand, in another study with three-barrel horses, an increase in serum iron was observed after a race but retuned to baseline val-ues at 30 minutes of recovery [47].…”
Section: Discussionmentioning
confidence: 99%